Long-term study of zooplankton biomass in the south- eastern part of the Gulf of Trieste (Adriatic sea) - Malej, Jan (Annales. Series historia naturalis, 2025)
We present a dataset of zooplankton biomass spanning more than four decades (1974–2019). The dry mass of zooplankton ranged from below 10 to almost 100 mg m-3, was highest in 1989–2002 and declined thereafter. The interannual variability of zooplankton dry mass in the period 1993–2018 was compared with the regional atmospheric index WeMOi, chlorophyll a and frequency of jellyfish blooms. Increased dry mass values were associated with a positive phase of the regional atmospheric index WeMOi, higher chlorophyll a and a lower frequency of jellyfish blooms.
Keywords: chlorophyll a; časovni niz; dry mass; jellyfish blooms; klorofil a; masovno pojavljanje medu; mrežni zooplankton; net zooplankton; suha masa; time series